Recent advances on the diversification of marine finfish species in Croatia - Skaramuca S.; Kozul V.; Glavic N.; Tutman P.; Glamuzina B.; Katavic I.; Grubisic L. (Recent advances in Mediterranean aquaculture finfish species diversification, 2000)
Research on the introduction of new finfish species to mariculture followed commercial development during the eighties in Croatia. Although a few species were under investigation, such as the common dentex, Dentex dentex, two-banded sea bream, Diplodus vulgaris, and sea bream, Diplodus puntazzo, the technology was not developed to a commercial level. In the meantime, following the recent interest for mariculture development in Croatia, more research was undertaken to diversify production and to add new species with a higher market value. There are about ten species in all of Croatia which are the subjects of mariculture research. In our laboratory, we chose the following species: groupers of the genus Epinephelus, amberjack, Seriola dumerili, pink dentex, Dentex gibossus, stone fish, Scorpaena scrofa, and some other species of lower commercial interest, but important for the repopulation of destroyed ecosystems, such as the brown wrasse, Labrus merula.
Seminar of the CIHEAM Network on Technology of Aquaculture in the Mediterranean on 'Recent advances in Mediterranean aquaculture finfish species diversification', 1999/05/24-28, Zaragoza (Spain)